Promoting communication in English classes through effective questioning - Karbašová, Tereza (Univerzita Pardubice, 2009)
The aim of the diploma thesis is to investigate the topics of communication and the effective questioning in a second language learning classroom. The taxonomy of educational objectives by Benjamin Bloom plays a crucial role in the practical as well as the theoretical part of the thesis. The Taxonomy serves as the basis for the classification of the questions from the research. Cílem diplomové práce je nastínit problematiku komunikace a efektivního dotazování ve výuce cizího jazyka. Taxonomie vzdělávacích cílů Benjamina Blooma hraje klíčovou roli jak v teoretické, tak i praktické části práce. Taxonomie tvoří základ klasifikace otázek výzkumu.
Efektivní otázka jako nástroj podpory komunikace při výuce anglického jazyka
Keywords: Komunikace; komunikativní kompetence; Bloomova taxonomie vzdělávacích cílů; kladení efektivních otázek; Výuka anglického jazyka; Communication; communicative competence; the Bloom's taxonomy of educational objectives; effective questioning; ELT